2008
DOI: 10.1093/qjmed/hcn137
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of captivity: health effects of far East imprisonment in World War II

Abstract: Though medical consequences of war attract attention, the health consequences of the prisoner-of-war (POW) experience are poorly researched and appreciated. The imprisonment of Allied military personnel by the Japanese during the World War II provides an especially dramatic POW scenario in terms of deprivation, malnutrition and exposure to tropical diseases. Though predominantly British, these POWs also included troops from Australia, Holland and North America. Imprisonment took place in various locations in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…10,11 Further susceptibility to neurotoxicity may be associated with certain micronutrient deficiencies, which needs to be explored. 12,13 Based on these findings in a small group, it may be difficult to make significant suggestions. It would be pertinent to asssess the possibility of enhanced genetic or environmental susceptibility of Indian children to the neurotoxic effects of vincristine in a larger study.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Further susceptibility to neurotoxicity may be associated with certain micronutrient deficiencies, which needs to be explored. 12,13 Based on these findings in a small group, it may be difficult to make significant suggestions. It would be pertinent to asssess the possibility of enhanced genetic or environmental susceptibility of Indian children to the neurotoxic effects of vincristine in a larger study.…”
Section: Discussionmentioning
confidence: 99%
“…The dilated pupil observed among zoo monkeys compared to wild monkeys reflects higher sympathetic activity, 24,28 which may be due to captivity-related stress. [30][31][32] Despite the best welfare measures adopted, nothing can fully replace a natural habitat, hence several studies have reported stress among captive exotic animals. [30][31][32] Furthermore, the reliability of pupil diameter as a reflection of autonomic system activity ( Figure 2) and mental stress has previously been demonstrated in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Despite the best welfare measures adopted, nothing can fully replace a natural habitat, hence several studies have reported stress among captive exotic animals. [30][31][32] Furthermore, the reliability of pupil diameter as a reflection of autonomic system activity ( Figure 2) and mental stress has previously been demonstrated in humans. 3,5,[24][25]27,33 The feasibility to non-invasively and objectively quantify stress based on iris/pupil area ratio in our opinion has potential to be of utility in personalised animal welfare measures.…”
Section: Discussionmentioning
confidence: 99%
“…During the next 3½ years, the POWs were moved to various other locations, including Japan, to work in the dockyards and factories; and Thailand and Burma to construct the notorious "Death Railway". As well as undertaking hard physical work and exposure to tropical infections (e.g., malaria, dysentery, cholera, dengue etc), there was a universal shortage of food which was of poor quality and low in protein and vitamins.Overall, about 25% of POWs died in captivity, [10] and many survivors suffered persisting ill health -including post-traumatic stress disorder in about 35%, [11] and long-term infection with the nematode worm Strongyloides stercoralis in 15%. [12] Burning feet in captivity FEPOWs from all areas of incarceration frequently complained of burning feet.…”
Section: Far East Pows and "Burning Feet"mentioning
confidence: 99%
“…In some locations, these were known as "electric feet" (to describe the shooting neuropathic pains) or "happy feet" (in relation to moving and stamping around to try to relieve the pain). Shortly after release in 1945, some POW medical officers recorded their experiences of the condition [9][10][11][12] in captivity. Later, BFS in FEPOWs was to be described as persisting many years after release.…”
Section: Far East Pows and "Burning Feet"mentioning
confidence: 99%